Macroeconomic Volatility : The Policy Lessons from Latin America - Singh, Anoop (IMF Working Papers; Working Paper ;, 2006)
The recent recovery in Latin America has been impressive but also raises the question whether this represents a fundamental break with the region's history of boom-bust cycles. The paper traces how this history of macroeconomic volatility and financial crisis over the past century has adversely impacted on growth and other development indicators, and the role played by policy instability. The paper then concludes that recent policies in the region offer encouragement that these vulnerabilities are being addressed, but notes that an important agenda still remains to be addressed.